2003
DOI: 10.1002/ddr.10158
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized candida cell Wall β‐glucan, CSBG, is an epitope of natural human antibody

Abstract: We have recently developed a protocol to obtain a soluble Candida spp. b1, 3-glucan (CSBG) by sodium hypochlorite (NaClO) oxidation and subsequent dimethyl sulfoxide (DMSO) extraction. CSBG is composed mainly of b-1,3 and b-1,6-glucosidic linkages with a small amount of branching. Antibody to b-glucan is generally difficult to produce. In the present study, the specificity of the human sera to CSBG was examined by ELISA. Using CSBG-coated plates, sera from normal human volunteers showed high reactivity that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…On the other hand, we recently reported that the antibody to solubilized Candida cell wall b-glucan (CSBG) having b-1,3 and b-1,6glucosidic linkages, was detected in sera of Candida immune mice and human sera. 8,9) From this evidence, it was suggested that not all b-glucans were weak immunogens.…”
mentioning
confidence: 99%
“…On the other hand, we recently reported that the antibody to solubilized Candida cell wall b-glucan (CSBG) having b-1,3 and b-1,6glucosidic linkages, was detected in sera of Candida immune mice and human sera. 8,9) From this evidence, it was suggested that not all b-glucans were weak immunogens.…”
mentioning
confidence: 99%
“…Since ABA levels vary across the human population [1113], we sought to characterize whether differences in ABA levels may influence Imprime binding. In sera from 143 healthy human volunteer subjects, binding of Imprime in WB was correlated to IgG (independent of IgM) or IgM (independent of IgG) ABA levels measured in the serum from the same blood draw.…”
Section: Resultsmentioning
confidence: 99%
“…7) The anti-CSBG antibody recognizes the straight chain b6 structure of b glucan, and its specific immune responses to b glucan were confirmed using an inhibition test. As shown in Fig.…”
Section: Anti-b Glucan Antibody As a Marker Predicting Mycosis Includmentioning
confidence: 90%
“…The measurement of the anti-CSBG antibody in patients with AAV is useful for evaluating the natural or acquired immune capacity of the host against b glucan and predicting the development of deep-seated mycosis as a complication, and this antibody titer can be a clinical parameter for optimal immunosuppressive therapy for AAV and anti-infection measures. 7,8) As shown in Fig. 4, AAV frequently develops in aged people, and induces systemic vasculitis causing disorders in the kidneys and respiratory organ as two major vital organs.…”
Section: Risk Factors For Infection In Aav Patientsmentioning
confidence: 99%